2020
DOI: 10.1108/jacpr-04-2020-0493
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between parenting styles and peace attitudes

Abstract: Purpose Taking into account previous literature on the role that the parenting styles to which individuals are exposed to during childhood have in shaping prosocial behaviors and attitudes, this study aims to investigate the relationship between parenting styles of parents and peace attitudes. Design/methodology/approach The peace attitude and the parenting style questionnaires were completed by 358 adolescent and adult participants. Pearson correlation coefficients were extracted and a stepwise multiple reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…This study's findings are consistent with prior research, indicating that specific personality traits significantly influence sustainable behaviors. As suggested by earlier studies [6,[29][30][31]39] the present study confirms that agreeableness and openness are primary predictors of sustainable behaviors. Individuals with high levels of agreeableness tend to be cooperative, empathetic, and accommodating [39], fostering prosocial and environmentally friendly behaviors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study's findings are consistent with prior research, indicating that specific personality traits significantly influence sustainable behaviors. As suggested by earlier studies [6,[29][30][31]39] the present study confirms that agreeableness and openness are primary predictors of sustainable behaviors. Individuals with high levels of agreeableness tend to be cooperative, empathetic, and accommodating [39], fostering prosocial and environmentally friendly behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…Understanding the motivations behind environmentally friendly behavior is crucial, especially in the face of growing awareness of climate change and the urgent need for concrete actions. Previous research has uncovered various factors associated with ecological attitudes and behaviors, including locus of control, personal responsibility, economic orientation, moral norms, social norms, intention, and feelings of guilt [6,[29][30][31][32][33][34]. Personality traits have also been linked to ecological attitudes and behaviors [35].…”
Section: Factors Influencing Environmentally Friendly Behaviormentioning
confidence: 99%
“…Summarizing, research consistently shows that authoritative parents tend to promote a healthy and prosocial development of their children. According to previous research, individuals who rated their parents higher in authoritative parenting will show higher peace attitudes scores (Canegallo et al, 2020). We believe that parenting can also be associated with creativity, and, at present, no one has studied the relationship between the two.…”
Section: Overviewmentioning
confidence: 87%
“…Recent literature has investigated the relationship between different personality factors and peace attitudes. Canegallo et al (2020), for example, found that Conscientiousness, Openness to Experience, Emotional Stability, and Agreeableness are associated with peace attitudes. Guilfoos and Kurtz (2017) showed that social information is used in cooperative game strategies with the Prisoner’s Dilemma game.…”
mentioning
confidence: 99%